Perancangan Proses Manufaktur Mesin Kompos Cair dari Sampah Buah - A. M. Nurul Hidayat; Estu Prayogi (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
Many people use rotten / unfit fruit to make liquid compost with fruit aroma to fertilize their plants, processing fruit that is not suitable for use which will be reprocessed to reduce fruit waste in anticipation of health problems, especially when rotten fruit is thrown away Careless places will cause problems for public health however, their tools are not efficient for processing the fruit because the cutting process is still using a kitchen knife so that the production of fruit which is made into liquid compost is slow in production, so a liquid compost machine from fruit waste is needed to speed up production making compost and making more production and processing faster. The purpose of this study was to design a manufacturing process based on the design drawings of a liquid compost machine from fruit waste. The method used is Design for Manufacturing and Assembly (DFMA). The output of this method is a Standard Operational Procedure (SOP) document and an Operation Process Chart (OCP). Based on the calculation results of the liquid compost machine manufacturing process design, the net estimate of manufacturing process time is 392 minutes with a total of 66 activities consisting of operation, assembly and inspection activities.